JELLY NENAS DENGAN PENAMBAHAN KARAGENAN DAN SUKROSA (The making Pineapple Jelly used Carrageenan and Sucrose Addition) (Jurnal Teknologi Pangan, 2015)
ABSTRACT   Pineapple is one of the horticultural commodity, has acid until sweet taste and vitamine C. Jelly is semi crammed food made from fruit juice with sucrose, acid and carrageenan addition. Research aim on the effect of carrageenan and sucrose addition on the quality of pineapple jelly has been conducted. This research used randomixed completely design consisting of two factors and two replications. The frist factor is carrageenan addition (0,5%; 0,75%; 1,00% and 1,25%) and the second factor is sucrose addition (25%, 30%, 35% and 40%). The best treatment is combination of carrageenan 1,00% and sucrose 30%. This pineapple jelly product has reduction sugar 1,97%, vitamine C 4,98 mg, water activity 0,91%, texture 1,78 mm/gr. det, taste score 4,0 and color score 4,3.   Keyword :jelly, carrageenan, sucrose, fruit juice.     ABSTRAK   Buah nenas merupakan salah satu komoditas hortikultural, mempunyai rasa masam sampai manis dan mengandung vitamin C. Jelly adalah makanan semi padat, terbuat dari sari buah dengan tambahan sukrosa, asam dan karagenan. Tujuan dari penelitian ini untuk mengetahui pengaruh dari penambahan karagenan dan sukrosa agar dihasilkan helly nenas yang bermutu.Rancangan penelitian menggunakan rancangan acak lengkap faktorial, dua faktor dan dua ulangan. Faktor pertama penambahan karagenan (0,5%; 0,75%; 1,00% dan 1,25%) dan faktor kedua penambahan sukrosa (25%, 30%, 35% dan 40%). Hasil penelitian terbaik pada kombinasi karagenan 1,00% dan sukrosa 30%, produk jelly nenas mempunyai gula reduksi 1,97%, vitamin C 4,98 mg, Aw 0,91%, tekstur 1,78 mm/gr. det, nilai rasa 4,0 dan nilai warna 4,3.   Kata kunci : jelly, karagenan, sukrosa, sari buah.